2022
DOI: 10.1038/s41598-022-10394-7
|View full text |Cite
|
Sign up to set email alerts
|

Tuning riboflavin derivatives for photodynamic inactivation of pathogens

Abstract: The development of effective pathogen reduction strategies is required due to the rise in antibiotic-resistant bacteria and zoonotic viral pandemics. Photodynamic inactivation (PDI) of bacteria and viruses is a potent reduction strategy that bypasses typical resistance mechanisms. Naturally occurring riboflavin has been widely used in PDI applications due to efficient light-induced reactive oxygen species (ROS) release. By rational design of its core structure to alter (photo)physical properties, we obtained d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…For alternative irradiation durations (15 or 30 min), an improvement in control is not consistently observed. The observed variations in the latter results can be attributed to the following: (i) prolonged LED light exposure, resulting in faster riboflavin photodecomposition [31], and consequently, the efficacy diminishes over time; (ii) in the fruits where CH-RF was applied without initial LED light exposure, they were kept in a natural-light environment in the laboratory, rather than complete darkness. This result suggests the possibility of some activation of riboflavin taking place.…”
Section: Discussionmentioning
confidence: 99%
“…For alternative irradiation durations (15 or 30 min), an improvement in control is not consistently observed. The observed variations in the latter results can be attributed to the following: (i) prolonged LED light exposure, resulting in faster riboflavin photodecomposition [31], and consequently, the efficacy diminishes over time; (ii) in the fruits where CH-RF was applied without initial LED light exposure, they were kept in a natural-light environment in the laboratory, rather than complete darkness. This result suggests the possibility of some activation of riboflavin taking place.…”
Section: Discussionmentioning
confidence: 99%
“…Since SARS-CoV-2 requires an envelope homotrimeric spike glycoprotein (S) to interact with the cellular receptor ACE-2 [36], it was proposed that selective impairment of surface proteins, like spike glycoprotein (S), by PDI can effectively inhibit infectivity of SARS-CoV-2 [24,25,37]. Additionally, it was suggested that effectivity of antiviral PDI may, in part, be explained by a light-induced photocleavage reaction of viral ssRNA [38]. However, this occurs by light irradiation with much shorter wavelengths (345-420 nm).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these reports focus on the use of methylene blue or curcumin, requiring blue light for activation, which may pose significant risks and does not penetrate into deeper tissues. Often, surrogates (like Phage Phi6 [42] or HIV-based pseudotyped models [43], lentiviruses pseudotyped with the SARS-CoV-2 Spike [44], murine hepatitis virus [38], alphacoronavirus HCoV-229E or the betacoronavirus HCoV-OC43 [44]) were used instead of SARS-CoV-2 isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, lumichrome, the product of light-induced or enzymatic degradation of riboflavin, appeared to be selective towards bacteria, being ten times more effective against Gram-positive bacteria than against Gram-negative bacteria [ 87 ]. Recently, Crocker et al [ 98 ] showed that the use of LED light (1 × 10 5 lux) and flavin with a bromine atom in the structure, increases the production of singlet oxygen through a heavy-atom effect, resulting in an increased PDT effect against both bacteria and viruses. This inspiring research may result in the design of a new generation of flavins.…”
Section: Riboflavin and Its Derivates In Pdt: Biological Issuesmentioning
confidence: 99%